The Leadership of School Principal in The Education Era 4.0 - Ashdaq Fillah FR; Erny Roesminingsih; Meini Sondang Sumbawati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Terminologically, the word 'leader' comes from the word "lead" which means to guide/to give guidance. Etymologically, a leader is a person or figure who has the ability to influence or persuade other parties to take action so as to achieve common goals. Thus, a leader is someone who is able to lead, that is to control, guide, direct, and influence others to take action in order to achieve a specified goal. The school principal can be defined as the leader of the school or institution where lessons are given and received. Currently, the world is entering what is called the Industrial Revolution 4.0., thus education in Indonesia is also leaning towards it. As a leader, there are several characteristics of the principal that are in line with this era of education 4.0. The principal must be creative, innovative, open, and able to make the right decisions against all changes and demands in the 4.0 era.